COVID-19 and Fungal Diseases - Kyoung-Ho Oh; Seung-Hoon Lee (Antibiotics, 2022)
Coronavirus Disease-2019 (COVID-19) can cause secondary bacterial and fungal infections by affecting the expression of pro-inflammatory markers, such as tumor necrosis alpha and certain cytokines, as well as the numbers of CD4 and CD8 cells. In particular, in the head and neck, various fungal species are naturally present, making it the main route of secondary infection. It is difficult to clearly distinguish whether secondary infection is caused by COVID-19 directly or indirectly as a result of the immunocompromised state induced by drugs used to treat the disease. However, the risk of fungal infection is high in patients with severe COVID-19, and lymphopenia is observed in most patients with the disease. Patients with COVID-19 who are immunosuppressed or have other pre-existing comorbidities are at a significantly higher risk of acquiring invasive fungal infections. In order to reduce morbidity and mortality in these patients, early diagnosis is required, and treatment with systemic antifungal drugs or surgical necrotic tissue resection is essential. Therefore, this review aimed to examine the risk of fungal infection in the head and neck of patients with COVID-19 and provide information that could reduce the risk of mortality.